Cáscaras de cacao (Theobroma cacao L.) y estrategias de valoración ambiental en el sitio Guabal de la Parroquia Quiroga - Zambrano Cobeña, Jonathan Esteban (2023)
The objective of this research was to establish strategies for the valuation of cocoa shells (Theobroma cacao L.) according to their physicochemical and functional characteristics at the Guabal site in Quiroga parish, Bolivar canton, as a contribution to the circular economy. The current situation of the cocoa-producing farms of the Guabal site was diagnosed. Subsequently, the physicochemical and functional composition of cocoa shells was determined, and environmental valuation strategies were established based on their physicochemical and functional characterization. The methodology applied corresponds to a non-experimental transectional study, using inductive, deductive and analytical-synthetic methods; and techniques such as observation, interview and survey. The results show that the productive activities do not generate highly significant environmental impacts, only significant (30.30%), negligible (56.06%) and beneficial (13.64%) impacts. The physicochemical and functional characterization reports that this residue has 10.57% moisture; 2.15% crude protein; 0.31% ethereal fat; 24.90% crude fiber; 10.08% ash; 137.55 mg Equivalent Gallic Acid/ 100g sample of Total Polyphenol Content; 51.05% NDF; 40.49% FDA; 10.55% Hemicellulose; and 52.00% ELN. Therefore, the valuation strategies for this by-product based on the provisions of the Circular Economy White Paper of Ecuador and Agenda 2030, are framed in obtaining new pharmaceutical, medical, nutraceutical or functional food by-products of high commercial and environmental interest for the cocoa sector, which contribute to the fulfillment of Sustainable Development Goals 6, 7, 11 and 12.